(untitled) - Cook, Roy A. (Harlow, England, 2018)
The engaging writing style and hundreds of updated industry examples make Tourism: The Business of Hospitality and Travel, 6/​e, the perfect textbook for students taking their first hospitality or tourism class. It views the industry from a holistic, global business perspective - examining the management, marketing and finance issues most important to industry members. Chapters reveal an integrated model of tourism and address consumer behavior, service quality, and personal selling. The thoroughness of content and references also make it suitable for upper-level hospitality and tourism courses. Readings and integrative cases close each part, and end-of-chapter exercises allow students to apply their knowledge and refine their problem-solving and critical-thinking skills. This edition includes new and updated material on social media, event management, timeshares, sustainable and marijuana tourism, and the future of tourism.
Keywords: Du lịch,Tourism